Reliability Effects of Maintenance on TNEP Considering Preventive and Corrective Repairs - Mahdavi, Meisam; Monsef, Hassan; Romero, Ruben [UNESP] (Ieee-inst Electrical Electronics Engineers Inc, 2017)
The aim of this paper is to investigate maintenance effects on system reliability and transmission network expansion planning considering line loading and repairs. For this purpose, the maintenance cost is formulated taking into account transient and permanent forced outage rates, as well as durations of planned and forced outage. Also, transmission reliability is modeled considering load shedding (LS) and energy not supplied (ENS) criteria. LS index is calculated for transient forced outages and ENS criterion is computed for permanent forced outages, and planned outage rates and durations. Furthermore, the effects of line loadings on transmission system reliability are formulated through the transient and permanent forced outage rates. The proposed model was tested on the IEEE 24-bus and 30-bus test systems, and the results are discussed.
Keywords: Corrective and preventive repairs; forced and planned outages; line loading; line maintenance; TNEP